AU-IBAR uses feed assessment modelling to support Nigeria and Cameroon livestock investments - Mutua, John Y.; Baltenweck, Isabelle; Teufel, Nils; Amole, Tunde A.; Paliwal, Ambica; Cherotich, Fredah; Duncan, Alan J. (International Livestock Research Institute, 2025)
Here we report the results of a feed assessment and feed balance modelling exercise conducted by the International Livestock Research Institute (ILRI) and partners to guide livestock decisions in Nigeria and Cameroon. The work was commissioned by the African Union Inter-African Bureau for Animal Resources (AUIBAR) who reported the hand-over of the national feed balance and inventory to the Nigeria Federal Ministry of Livestock Development and the National Bureau of Statistics. A similar process is underway for Cameroon.